Parametric Study of Methanation Performance on Ru/Na2O/Al2O3 Dual-Function Materials - Andrea Strazzolini; Andrea Braga; Maila Danielis; Sara Colussi (Chemical Engineering Transactions)
The development of Dual-Function Materials (DFMs) for the combined CO2 capture and valorization is gaining increasing attention due to its process intensification approach and promising advantages in terms of energy requirements. Significant efforts are devoted to optimizing materials and process configuration, but on both sides many issues still remain open. In this work the behavior of dry milled Ru/Na2O Dual-Function Materials on an alumina-based support with different methanation kinetics is evaluated for the coupled CO2 capture and hydrogenation to methane. In particular, the duration of the methanation step is changed to investigate its effect on the overall efficiency of the material, measured in terms of both CH4 yield and H2 conversion. The results show that, by opportunely tuning this parameter, it is possible to increase the average specific methane production rate by a factor of 1.9 or 2.6, the improvement being all the more significant the faster the CO2 methanation kinetics, increasing also the noble metal utilization efficiency.